Wind Engineering Analysis of Parabolic Trough Collectors to Optimise Wind Loads and Heat Loss. (May 2015) - Paetzold, J.; Cochard, S.; Fletcher, D.F.; Vassallo, A.
Abstract: Concentrating Solar Power (CSP) plants tend to be located in open areas. This leads to the power plant usually being subjected to high wind speeds without much shelter or protection. In parabolic trough plants the solar field, the collectors and receiver tubes, are affected by the wind on both the structural, as well as the performance level. The collectors must resist the aerodynamic forces caused by the wind, and the airflow around the receiver tube has a cooling effect on it. The effects of the wind on Parabolic Trough Collectors (PTC) were investigated in a parametric study over a large range of pitch and yaw angles. Three different trough geometries were analysed varying the focal length of the parabola, i.e. the depth of the trough. The data were obtained using the Computational Fluid Dynamics (CFD) package ANSYS CFX 15.0 and validated against experimental data. An increase of the depth of the parabolic trough increases the maximum aerodynamic forces on the trough. However, a deeper trough has a sheltering effect on the receiver tube, thus reducing the thermal losses due to forced convection. This effect becomes more important the higher the temperature difference between the receiver and ambient air, and it can also reduce the requirements for highly insulated evacuated receiver tubes, which are a significant cost factor in PTC plants. The highest force coefficients on the PTC are observed at high positive pitch angles and a yaw angle of 0°. While the aerodynamic loads on the trough reduce significantly with an increase in the yaw angle of the approaching wind, the heat flux around the receiver tube only shows a slight decrease in most cases. At some negative pitch angles an increasing yaw angle leads to higher thermal losses, as a vortex, forming at the leading edge of the trough, causes high air velocities around the receiver.